2001
DOI: 10.5458/jag.48.317
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Pasting Properties of Legume Starches.

Abstract: The molecular structures and pasting properties of four legume starches (white Dutch runner; WDR, adzuki bean, pea and common bean) were examined. The apparent amylose content (27 .0-30.0%) was 3.9-9.4% higher than the actual amylose content (17.6-25.5%) due to the high iodine affinity (IA) of the legume amylopectins. The crystalline type of pea starch was of Cb and those of the others were of the Cc. Adzuki bean starch had the highest maximum viscosity and breakdown. No breakdown was observed for pea starch. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The first two peaks correspond to amylopectin and the 11.90 ± 0.16b 12.79 ± 1.09b 11.28 ± 0.11a 11.42 ± 0.17a third represents amylose (Grant et al, 2002). The amylose content in bean starches varied from 23.20 to 28.06% (Table 1) and was similar to values reported for common bean (Yoshimoto, Matsuda, Hanashiro, Takenouchi, & Takeda, 2001). Significant differences (P > 0.05) between varieties were observed in amylose content for varieties grown under irrigation, but not for varieties grown under rain fed conditions.…”
Section: Chemical Composition and Amylose And Amylopectin Content Detsupporting
confidence: 77%
“…The first two peaks correspond to amylopectin and the 11.90 ± 0.16b 12.79 ± 1.09b 11.28 ± 0.11a 11.42 ± 0.17a third represents amylose (Grant et al, 2002). The amylose content in bean starches varied from 23.20 to 28.06% (Table 1) and was similar to values reported for common bean (Yoshimoto, Matsuda, Hanashiro, Takenouchi, & Takeda, 2001). Significant differences (P > 0.05) between varieties were observed in amylose content for varieties grown under irrigation, but not for varieties grown under rain fed conditions.…”
Section: Chemical Composition and Amylose And Amylopectin Content Detsupporting
confidence: 77%
“…i Biliaderis et al (1979). j Sandhu and Lim (2008), Ratnayake et al (2001), Yoshimoto et al (2001), Biliaderis et al (1979), Colonna and Mercier (1979). k Biliaderis et al (1979), Colonna and Mercier (1984 molecule.…”
Section: Structure Of Amylose and Amylopectinmentioning
confidence: 95%
“…The thermal stability of cross-linked starches would be of value where increased thermal stability is required at low pH or under the high temperature conditions of pressure cooking and sterilization. Yoshimoto et al (2001). b Hoover and Ratnayake (2002) and Hoover and Sosulski (1985a).…”
Section: Modified Pulse Starchesmentioning
confidence: 96%
See 1 more Smart Citation
“…Extensive research has been done to study the chain length profile of amylopectin from different starch sources, such as maize (Takeda et al, 1988;Jane eta!., 1999), barley (Tang et al, 2001 a, b;Song and Jane, 2000;Jane et al, 1999;Yoshimoto et al, 2000Yoshimoto et al, , 2002MacGregor and Morgan, 1984), rice Hanashiro et al, 1996;Takeda et al, 1987b), wheat Shibanuma et al, 1994;Franco et al, 2002;Hizukuri and Maehara, 1990), tapioca , sweet potato (Hanashito et a!., 1996;McPherson and Jane, 1999) and legumes (Biliaderis, 1982b;Biliaderis et al, 1981;Ratnayake et al, 2001;Yoshimoto et al, 2001). The resulting chromatography showed that debranched amylopectin usually exhibits a trimodal or polymodal distribution pattern.…”
Section: Chain Length Distributionmentioning
confidence: 99%